Adobe Photoshop CS6 on demand - Johnson, Steve, 1961- (On demand (Indianapolis, Ind.), 2012)
Need answers quickly? Adobe Photoshop CS6 on Demand provides those answers in a visual step-by-step format. We will show you exactly what to do through lots of full color illustrations and easy-to-follow instructions. Numbered Steps guide you through each task See Also points you to related information in the book Did You Know alerts you to tips and techniques Illustrations with matching steps Tasks are presented on one or two pages Inside the Book Improve productivity with the CS6 adjustable interface and templates Use automatic saving options for better efficiency and protection Use automatic layer alignment and blending to work with objects Use more precise color correction to enhance a photo Use content-aware options for scaling and fill Create eye-catching images with special effect filters Transform plain text into a showstopping image Create character and paragraph styles to manage and use text Transform video in Photoshop justlike an image Create and manipulate 3D models using presets and custom options.